IMPROVING STUDENTSâ€™ WRITING RECOUNT TEXT THROUGH PROJECT- BASED LEARNING - Listia Dalpah Nursalimah; Tanto Setia Muljanto (Institut Pendidikan Indonesia Garut, 2020)
This research is entitled â€œIMPROVING STUDENTSâ€™ WRITING RECOUNT TEXT THROUGH PROJECT-BASED LEARNINGâ€. This research aimed to examine improving studentsâ€™ writing recount text through Project-Based Learning method. The research employed quantitative research with quasi- experimental design. The participants in this research were 30 students in experimental class and 30 students in control class in one of senior high school in Garut. In collecting data, the reseacher used test pre-test and post- test. The data were analyzed statistically using Mann-Whitney test. The result of Project-Based Learning method gave significant improvement to studentsâ€™ writing proficiency. This result gained from hypothesis testing showed that Z18.0948 > Z5.1885. In, conclusion Ho was rejected and Ha was accepted. It means that there is a significant difference in the achievement of the students who are through by Project-Based Learning.